Correlation between hatchability traits, moisture loss, and embryonic mortality in commercial Lohmann Brown Lite breeder birds in South Africa - Mpofu, Takalani J.; Masia, Khathutshelo Simon; Idowu, Ayodedji Peter (Jurnal Sain Peternakan Indonesia, 2025)
This study aimed to determine the relationship between hatchability traits, moisture loss and mortality in commercial Lohmann Brown Lite breeders in South Africa. A total of 5400 hatchable eggs were incubated. Descriptive analysis and the Pearson correlation coefficient were computed using MiniTab17. Fertility, embryo livability and mortality, total moisture loss, and hatchability were 95.06%, 86.56%, 6.37%, 13.27%, and 93.63%, respectively. There is a positive correlation between egg fertility and embryo livability (p<0.001; r=0.86) and between egg fertility and hatch of all set (r=0.82). There is a positive correlation between embryo livability and hatch of all sets (p < 0.001; r = 0.81). A negative correlation exists between moisture loss during days 0-10 and 11-18 of incubation (p < 0.001; r = -0.64). A positive correlation between total moisture loss and that during days 0-10 (p<0.01; r=0.44) and 11-18 (p<0.05; r=0.41) exists. A negative correlation was observed between hatch of fertile eggs and moisture loss (p < 0.05; r = 0.32). First-grade yield shows a positive correlation with total pullet yield (p < 0.001; r = 0.95). First-grade pullet yield has a negative correlation with male yield (p < 0.001; r = -0.95). Second-grade pullet yield has a positive correlation with overall pullet yield (p<0.05; r=0.36). Second-grade pullet yield has a negative correlation with male yield (p<0.05; r=-0.36. These results indicate that hatchability, embryonic mortality, and moisture loss are strongly influenced by fertility and incubation conditions. Optimizing these factors through proper management can improve chick quality, enhance hatchery efficiency, and increase productivity and profitability, contributing to sustainable poultry production and national food security.